The impact of cannabis legalization for recreational purposes on youth: A narrative review of the Canadian experience - Rubin-Kahana, Dafna Sara; Crépault, Jean-François; Matheson, Justin; Le Foll, Bernard (Frontiers in Psychiatry, 2022)
Cannabis legalization for non-medical purposes (subsequently referred to as “cannabis legalization” or “legalization”) took place in Canada in October 2018. One of the federal government's stated goals with cannabis legalization was to protect Canadian youth from cannabis-related harms. The main objective of this narrative review is to describe the impact of cannabis legalization on Canadian youth. To that end, we discuss the regulation of the Canadian cannabis market, outline changes in the epidemiology and parameters of cannabis use (modes of use, potency of cannabis) among youth, and discuss prevention and education initiatives related to cannabis. The Canadian model differs from other jurisdictions that legalized recreational cannabis use, especially with regard to a higher degree of government regulation of the cannabis market. Another difference is the development and endorsement of lower-risk cannabis use guidelines to educate the public and health professionals. The results available for this review cover only 3 years post-legalization. Cannabis legalization in Canada brought an apparent increase in use among Canadian older than 25. However, results for youth are mixed, with the majority of studies showing no pronounced increase. Notably, the trend of a decrease in adolescents' cannabis use seen pre-legalization may have reversed. Emerging evidence also suggests that cannabis-related hospitalizations and emergency department visits among Canadian youth may have increased due to cannabis legalization. Data about changes in the age of initiation, the influence of legalization on sex and gender, and race/ethnicity are limited, with evidence suggesting that the age of initiation slightly increased. So far, there is limited data about the impact of cannabis legalization on Canadian youth. Further long-term monitoring and research to assess the effects of cannabis legalization on Canadian youth.